2008
DOI: 10.1007/s00246-008-9331-z
|View full text |Cite
|
Sign up to set email alerts
|

Universal Screening for Extracardiac Abnormalities in Neonates with Congenital Heart Disease

Abstract: Extracardiac or genetic abnormalities (EGA) represent a factor in the morbidity of patients with congenital heart disease. We evaluated the way neonates with CHD are screened at our institution and determined the yield for the screening tests. We reviewed the charts of 223 neonates with structural CHD. Subjects were categorized into 6 groups: univentricular, left-sided obstructive lesions, right-sided obstructive lesions, septal defects, conotruncal defects (CTD), and other. We reviewed which patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 16 publications
5
35
3
1
Order By: Relevance
“…Besides when we compared the CHD patients with controls without suspicion of a urinary tract abnormality, the result presented an even more pronounced significance. The lower frequency of abdominal abnormalities observed in our study among CHD patients, compared to Gonzalez et al 9 , could be due to the fact that our patients with CHDs were not restricted to newborns and also that all subjects underwent AUS, regardless of clinical suspicion. In the study of Muragasu et al 10 , the patients were submitted only to the ultrasound study of the urinary tract, and 11.9% clinically significant abnormalities were found.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Besides when we compared the CHD patients with controls without suspicion of a urinary tract abnormality, the result presented an even more pronounced significance. The lower frequency of abdominal abnormalities observed in our study among CHD patients, compared to Gonzalez et al 9 , could be due to the fact that our patients with CHDs were not restricted to newborns and also that all subjects underwent AUS, regardless of clinical suspicion. In the study of Muragasu et al 10 , the patients were submitted only to the ultrasound study of the urinary tract, and 11.9% clinically significant abnormalities were found.…”
Section: Discussioncontrasting
confidence: 73%
“…The urinary tract malformations were also prevalent in the study of Bosi et al 22 , Stephensen et al 25 , Amorim et al 28 and Gonzalez et al 9 . Genitourinary tract abnormalities were found from 7.4 to 15.1% of patients with CHD in different series 18,20,24,26 and in 15.2% of live births and in 25.3% of stillbirths in the study of Amorim et al 28 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Another study reported a 42% incidence of abnormalities on HUS, with the majority having ventriculomegaly or enlargement of the subarachnoid space, LSV, or calcifications in the basal nuclei. 8 Gonzalez et al 9 reported that 21% of infants with CHD had significant or marginally significant abnormalities on HUS. One of the most frequently cited articles about findings on HUS in CHD indicates an incidence of brain injury of 59% diagnosed with HUS, with the majority again demonstrating LSV and/or cerebral atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the overall detection rates of brain injury in infants with CHD range from 5% to 59% in the multiple studies performed. [7][8][9][10][11] Over the past decade, the use of MRI in infants with CHD has been increasing, although mostly in the research setting. A number of studies have reported the rate of preoperative brain injury on MRI in young infants undergoing surgery for CHD to be between 25% and 40%.…”
Section: What This Study Addsmentioning
confidence: 99%